Association between cardiac, renal, and hepatic biomarkers and outcomes in patients with acute heart failure. Issue 3 (26th May 2016) - Chan, Wing W.; Waltman Johnson, Katherine; Friedman, Howard S.; Navaratnam, Prakash
ABSTRACT: Objectives : Myocardial injury, worsening renal function, and hepatic impairment are independent risk factors for poor patient acute heart failure (AHF) outcomes. Biomarkers of organ damage may be useful in identifying patients at risk for poor outcomes. The objective of this analysis was to assess the relationship between abnormal AHF biomarkers and outcomes in AHF patients. Methods : AHF admissions (N = 104, 794) data from the Cerner Health Facts® inpatient database were analyzed retrospectively. Multivariate predictive models determined the impact of biomarkers on mortality, readmission, length of stay (LOS), and cost from index admission through 180 days post discharge. Thirty and 60 day time windows are reported but 180 day results were consistent with 60 day outcomes. Biomarkers evaluated were aspartate transaminase (AST), estimated glomerular filtration rate (eGFR), high sensitivity cardiac troponin, bilirubin, alanine transaminase (ALT), sodium, high sensitivity C-reactive protein (hs-CRP), uric acid, B-type natriuretic peptide (BNP), NT-ProBNP, blood urea nitrogen (BUN), serum creatinine (SCr), and hemoglobin. Results : All biomarkers evaluated except hs-CRP, uric acid, and NT-ProBNP were significant (p < 0.0001) predictors of mortality at all timepoints; non-significance for these 3 biomarkers is likely due to low patient counts (1%–2%). Odds ratios for significant biomarkers of mortality ranged from 1.168–2.076 at index admission, 1.205–1.946 at 30 days post-discharge, and 1.233–1.991 at 60 days post-discharge. AST, eGFR, troponin, ALT, BNP, BUN, SCr, and hemoglobin were significant (p < 0.0001) predictors of readmission risk at all timepoints. AST, eGFR, troponin, bilirubin, BUN, SCr, and hemoglobin were significant (p < 0.0001) predictors of cumulative LOS at all timepoints. AST, eGFR, troponin, ALT, sodium, BUN, and hemoglogin were significant (p < 0.0001) cost predictors at 30 and 60 days post-discharge. Conclusions : Renal function measures were associated with outcomes in patients hospitalized for AHF. Increased vigilance of renal biomarkers may be warranted to assess risk and promote proactive clinical management to improve outcomes.